Influence of Supervision Functions on Curriculum Implementation in Public Primary Schools in Turkana South Sub-County, Kenya - Samuel, Erumu Ekiru; Masinde, Dr. Robert; Amunga, Dr. Jane (IJRDO- Journal of Educational Research, 2021)
The headteachers’ key roles are to supervise the implementation of the curriculum and monitoring important instructional documents. This necessitated the current study. The research design employed was descriptive survey as it accurately described procedures and variables as well as the relationship between the variables to be predicted and identified. The population of the study consisted of 477 participants in Turkana South Sub County. Out of the 51 schools, 10 schools were selected to provide the sample schools which were randomly selected. The target population was 10 public primary school headteachers purposively sampled and 85 teachers sampled using systematic random technique in Turkana South Sub County. The research instrument used was the questionnaire and interview, whose variables were tested for content validity and reliability. The data analysis techniques used was descriptive statistics where the questionnaire were coded from 1-85, then categorization of responses into related themes as per the research objectives and finally description that involved explanations, narratives and descriptions of data. The statistics calculated were frequencies, mean, modes, percentages and standard deviations which helped to determine the proportions, averages scores and variances for each set of scores in the sample. From investigation, the findings and the recommendations will be used by various stakeholders in the education sector among them: the Ministry of Education, Basic Education Boards and other agencies to periodically conduct research or utilize the results of existing studies on headteachers’ curriculum as a guide for in-service training for the headteachers.